Essays on carbon taxation and food demand in Ireland - Verde, Stefano F. (Trinity College (Dublin, Ireland). Department of Economics, 2012)
This thesis is the collection of three applied studies, two of which deal with distributional effects of carbon taxation in the Irish economy and one, the third, which estimates a microeconometric model for food demand in Ireland. The two topics are treated separately and, while links between climate policy and food demand can certainly be found, the analyses do not converge. Originally, carbon pricing in Ireland was in fact the sole object of this project. However, as familiarity was gained with the Household Budget Survey (HBS), on which both the first two studies draw, it became clear that it was possible to extract useful and unexploited information on food demand from that source.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin.